Efektivitas Model Pembelajaran Hybrid Dalam Meningkatkan Pemahaman Agama Mahasiswa Di Era Digital - Rasyidin, Rasyidin; Raiyan, Raiyan; Anida, Anida; Nanda, Silvia (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Islamic Religious Education in the digital era faces challenges in adapting learning methods to technological developments. The hybrid learning model is an innovative solution that combines online and offline learning to improve student understanding. This research uses a pseudo-experimental method by comparing the experimental group that uses the hybrid model and the control group that learns conventionally. The results showed that students in the hybrid group experienced a significant increase in understanding, were more active in discussions, and had wider access to digital learning resources. However, challenges such as technological readiness and lecturer adaptation still need to be considered so that this method can be applied optimally.